Review of Law No 12 Of 2022 Concerning the Criminal Action of Sexual Violence Against the Custom Law of Forced Marriage in Indonesia: (Hifdz Nafs Analysis) - Nauval, Ahmad Zaky; Syukri Albani Nasution, Muhammad (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung, 2022)
Marriage is not only about forming a family that occurs because of the union of a man and a woman, but marriage is an inner and outer bond between a man and a woman as husband and wife with the aim to forming a family (household) that happy and eternal based on God Almighty. It becomes a problem if marriage is not based on the desire of each partner because the desire and feelings of mutual love are the main basic in carrying out a marriage. In practice, marriage coming from a coercion is not a new thing, in some areas it has even become customary law. By considering it the Indonesian government passed constitution number 12 of 2022 where forced marriage is categorized as a crime of sexual violence. However, there are still many rejections from several parties because of the conflict between the article and the provision of sharia and customary. By using the juridis-normatif method, this article will review this conflict. Forced marriages which are categorized as criminal acts in Indonesian have been ruled out in some areas by referring to customary provision that put forward the values of Maqashid Sharia. The result is that it is necessary to review Law No. 12 of 2022 that there are positive legal exceptions to customary law that apply in several regions of Indonesia, because the nature of the law itself aims to regulate and measure criminal punishment.